ANALYSIS OF THE RELATIONSHIP BETWEEN LEARNING INTEREST AND CRITICAL THINKING ABILITY ON ELEMENTARY SCHOOL STUDENTS’ MATHEMATICS ACHIEVEMENT - Agus Hari Sutrisno; Wasilatul Murtafiah; Jeffry Handika (RADJA PUBLIKA, 2026)
This study aims to analyze the relationship between learning interest and critical thinking skills on students’ mathematics achievement. The research subjects were 47 fifth-grade students from SDN Kedungrejo 1 and SDN Kropak 1 in Probolinggo Regency. Data were collected using test instruments and questionnaires, both of which were assessed through validity and reliability testing. The results confirmed that all instruments were valid and reliable for use in data collection. Furthermore, a normality test using the Kolmogorov–Smirnov method indicated that the data were normally distributed, with a significance value of 0.200, which exceeds the 0.05 threshold. The findings reveal that neither learning interest nor critical thinking skills has a significant relationship with fifth-grade students’ mathematics achievement at SDN Kedungrejo 1 and SDN Kropak 1. The significance values of the correlation were 0.580 for learning interest and 0.564 for critical thinking skills, both exceeding the 5% significance level. This indicates that these variables do not serve as direct predictors of mathematics achievement in this study. However, the analysis also shows that learning interest and critical thinking skills are strongly and significantly correlated with each other, with a correlation coefficient of 0.984 and a significance level of 0.001. This finding suggests that the two variables move in the same direction and mutually reinforce each other in the learning process, despite not directly influencing mathematics achievement.Therefore, this study indicates that students’ mathematics achievement at SDN Kedungrejo 1 and SDN Kropak 1 is likely influenced by other factors beyond learning interest and critical thinking skills, such as instructional quality, family support, intrinsic motivation, or foundational mathematical abilities.